Neuromuscular Coordination and Its Relationship with the Skills of Setting and Spiking among Football Tennis Players - Salman, Mais Mahmoud (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The aim of the current research was to examine the correlation between neuromuscular coordination and setting and spiking skills of football tennis players. The researcher used the descriptive approach in investigating the relationship between neuromuscular coordination and setting and spiking skills. The sample of the research was selective and composed of 45 youth players of the Specialized Football Tennis School in Baghdad Province with age of 16 years and above. The research sample was subjected to the relevant tests and the results obtained analyzed statistically to establish whether there is a relationship between neuromuscular coordination and setting skill on the one hand and neuromuscular coordination and spiking skill on the other. The primary finding of the study showed a positive correlation between neuromuscular coordination and setting as well as spiking skills among the football tennis players. Upon such findings, the researcher suggests that additional researches be carried out to investigate the effects of neuromuscular coordination on other skills in football tennis.